(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Cross cultural concerns became a significant ingredientof modern literature with the rise of modernist movement after the First WorldWar. Crossing the cultural borders involves conflict and also leads totransition in a country’s culture. R. Parthasarathy’s contribution to Englishpoetry is remarkable and unforgettable. He tries to create the lost order ofsociety and culture. This impulse to preserve his culture is at the bottom ofhis best known work Rough Passage. The present paper intends to explore thetraumatic cultural conflict through some of his poems from the Rough Passage.In the words of M.K. Naik, “R. Parthasarathy is a poet acutely conscious of thecomplex relationship between the hour glass of the Tamil mind and the exactchronometer of Europe.” The poet attempts to reconcile between the Tamil pastand the impotence felt in acquiring a foreign language.